Fabricating patch antennas within complex dielectric structures through multi-process 3D printing. (August 2018) - MacDonald, Eric; Espalin, David; Doyle, Derek; Muñoz, Jazmin; Ambriz, Steven; Coronel, Jose; Williams, Andrew; Wicker, Ryan
Abstract: In this work, a 3D printed patch antenna is fabricated within a complex dielectric structure relevant to the construction of satellites – an isogrid panel. The antenna was fabricated via a multi-process, hybrid, additive manufacturing system that included polymer material extrusion enhanced with complementary manufacturing capabilities of foil placement and patterning, wire integration and component placement. The antenna design targeted the commercial frequency of Bluetooth communication at 2.4 GHz by introducing a rectangular conductor of precise width, height and thickness from ground plane for the specific resonance. The measured reflection and gain coefficients were reasonable, however, two challenges were identified with the fabrication related to (1) imperfections typical of material extrusion additive manufacturing processes including unintentional porosity and (2) the insecure mechanical bonding between the output connector and substrate. Porosity impacted the dielectric features (permittivity) of the substrate and consequently introduced error in final antenna resonance (2.13 GHz versus the target of 2.4 GHz). The bonding affected mechanical reliability and caused changes in input impedance which affected signal quality for some orientations depending on cable flexing. Several remediations were identified, all of which included reinforcing the connector during embedding with a bonding agent. In the end, the antenna was compared to a commercial dipole antenna and the signal-to-noise ratios were within 6%.